Mangrove Ecosystem Vulnerability through Integrated Remote Sensing: A Systematic Literature Review - Rakhshanda Shaina Ahava Hidayat; Muhammad Iqbal Habibie; Ayang Armelita Rosalia (Institut Teknologi Sepuluh Nopember, 2026)
Mangrove ecosystems play a crucial role in maintaining the stability of coastal environments, but they face various pressures due to human activities and environmental changes that increase their vulnerability. This research aims to examine the development of remote sensing-based approaches in monitoring the condition, changes, and vulnerability of mangrove ecosystems, as well as to identify the main factors affecting their degradation. The method used is a Systematic Literature Review (SLR) with qualitative descriptive analysis of scientific publications related to mangrove monitoring using remote sensing technology. The study results show that remote sensing-based mangrove research has significantly increased, especially after 2010, along with the development of sensor technology, geographic information systems (GIS), and artificial intelligence methods. The main factors affecting the vulnerability of mangroves include anthropogenic pressures such as land conversion and pollution, environmental factors such as rising sea levels and hydrological changes, as well as biophysical factors related to the structure and condition of the vegetation. The integration of remote sensing, GIS, and spatial analysis has proven to enhance the effectiveness of monitoring and understanding the dynamics of mangrove ecosystem changes. Thus, an integrated geospatial approach becomes an important foundation in supporting the sustainable management and conservation of mangroves.